By which number?

Which number always divides n ( 2 n 2 + 7 ) n(2n^{2}+7) , where n n is any natural number?

None 7 2 3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Jordan Cahn
Feb 11, 2019

If n 0 m o d 3 n\equiv 0\bmod 3 then n ( 2 n 2 + 7 ) 0 m o d 3 n(2n^2+7)\equiv 0\bmod 3 . If n 1 m o d 3 n\equiv 1\bmod 3 or n 2 m o d 3 n\equiv 2\bmod 3 then n 2 1 m o d 3 n^2\equiv 1\bmod 3 . So n ( 2 n 2 + 7 ) n ( 2 + 7 ) m o d 3 0 m o d 3 \begin{aligned} n(2n^2+7) &\equiv n(2+7)\bmod 3\\ &\equiv 0\bmod 3 \end{aligned} Therefore n n is always divisible by 3 \boxed{3} .

Chew-Seong Cheong
Feb 11, 2019

We note that f ( n ) = n ( 2 n 2 + 7 ) f(n) = n(2n^2 + 7) is divisible by 3 for the first few n n 's. Let us prove that 3 f ( n ) 3 \mid f(n) for all natural number n n as follows.

All natural number n n can be represented as n = { 3 m if n m o d 3 = 0 3 m + 1 if n m o d 3 = 1 3 m 1 if n m o d 3 = 2 n = \begin{cases} 3m & \text{if } n \bmod 3 = 0 \\ 3m + 1 & \text{if } n \bmod 3 = 1 \\ 3m -1 & \text{if } n \bmod 3 = 2 \end{cases} , where m m is a natural number.

If n m o d 3 = 0 n \bmod 3 = 0 , then f ( 3 m ) = 3 m ( 2 ( 3 m ) 2 + 7 ) 0 (mod 3) f(3m) = 3m\left(2(3m)^2 + 7\right) \equiv 0 \text{ (mod 3)} .

If n m o d 3 = 1 n \bmod 3 = 1 , then

f ( 3 m + 1 ) ( 3 m + 1 ) ( 2 ( 3 m + 1 ) 2 + 7 ) (mod 3) ( 1 ) ( 2 ( 1 ) 2 + 7 ) (mod 3) 9 0 (mod 3) \begin{aligned} f(3m+1) & \equiv (3m+1)\left(2(3m+1)^2 + 7\right) \text{ (mod 3)} \\ & \equiv (1)\left(2(1)^2 + 7 \right) \text{ (mod 3)} \\ & \equiv 9 \equiv 0 \text{ (mod 3)} \end{aligned}

If n m o d 3 = 2 n \bmod 3 = 2 , then

f ( 3 m 1 ) ( 3 m 1 ) ( 2 ( 3 m 1 ) 2 + 7 ) (mod 3) ( 1 ) ( 2 ( 1 ) 2 + 7 ) (mod 3) 9 0 (mod 3) \begin{aligned} f(3m-1) & \equiv (3m-1)\left(2(3m-1)^2 + 7\right) \text{ (mod 3)} \\ & \equiv (-1)\left(2(-1)^2 + 7 \right) \text{ (mod 3)} \\ & \equiv -9 \equiv 0 \text{ (mod 3)} \end{aligned}

Therefore, 3 n ( 2 n 2 + 7 ) \boxed 3 \mid n \left(2n^2+7\right) for all natural numbers n n .

Chakravarthy B
Feb 10, 2019

Answer is 3.

Use Euclid division lemma by using (a=bq+r),b=3

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...